Analysis of HPV genotype differences in different stages of cervical intraepithelial neoplasia - YU Jingmin; CHEN Yan; YANG Xuewen (Shanghai yufang yixue)
ObjectiveTo explore the differences in human papillomavirus (HPV) genotype among patients with varying stages of cervical intraepithelial neoplasia (CIN).MethodsThis retrospective study included 113 patients with CIN who were treated at the Third People’s Hospital of Hangzhou from April 2020 to March 2023. The patients were divided into three groups based on the progression of CIN: CIN Ⅰ (n=30), CIN Ⅱ (n=42), and CIN Ⅲ (n=41). The influencing factors of CIN progression were analyzed, and HPV genotyping was performed logistic regression analysis was used to examine relationship between HPV genotypes and the degree of CIN progression, and the interaction between HPV genotypes and CIN progression-related factors were assessed.ResultsHPV genotype analysis revealed that HPV16, HPV58, HPV18, and HPV52 were the most common genotypes among CIN patients. The proportion of negative HPV cases in CIN I patients (53.33%) was significantly higher than that in CIN Ⅱ (33.33%) and CIN Ⅲ (0) patients. The infection rates and multiple infection rates of HPV16, HPV58, HPV18, and HPV52 (3.33%, 3.33%, 0, 0, 0.) were significantly lower in CIN Ⅰ patients compared to CIN Ⅱ (7.14%, 4.76%, 2.38%, 4.76%, 2.38%) and CIN Ⅲ patients (24.39%, 19.51%, 12.20%, 14.63%, 12.20%) (P<0.05). After adjusting for confounding factors, HPV16, HPV18, HPV52, and HPV58 remained significantly associated with the progression of CIN (P<0.05). Having ≥2 sexual partners (OR=3.529, 95%CI: 2.756~6.925, P=0.025), abnormal discharge odor (OR=5.684, 95%CI: 2.439~8.942, P=0.036), contact bleeding (OR=2.679, 95%CI: 1.627~3.192, P=0.018), and chronic cervicitis (OR=3.894, 95%CI: 1.952~4.931, P=0.031) were independent factors influencing the progression of CIN. HPV16, HPV18, HPV52, HPV58 exhibited positive interactions with the number of sexual partners, abnormal discharge odor, contact bleeding, and chronic cervicitis (P<0.05).ConclusionHPV16, HPV58, HPV18, and HPV52 are the most common genotypes of HPV infection in CIN patients, which are positively correlated with the degree of CIN progression. These genotypes are also closely related to factors influencing CIN progression.